Adherence to antimalarial chemoprophylaxis among Israeli travelers visiting malaria-endemic areas. Issue 44 (November 2021) - Khoury, Sobhi; Kaplan, Shiran; Zaidenstein, Ronit; Cohen, Erica; Tischler-Aurkin, Dinni; Sheffer, Rivka; Mathew, Lewis; Mor, Zohar
Abstract: Background: Travelers are recommended to take antimalarial chemoprophylaxis (AMC) when traveling to endemic areas. Methods: This prospective comparative cohort study included 400 Israeli travelers to malaria-endemic areas, recruited in pre-travel clinics. They were contacted within one month following their return and asked about their actual adherence and the reasons for non-adherence. Results: Of 400 travelers with a mean age of 24.6 [SD = 4] years, 201 (50.2%) were men and 328 (82%) were singles. The majority (N = 185, 46.3%) traveled with friends, and the most common travel destination was southeast Asia (N = 267, 66.8%). Most travelers (N = 340, 85%) did not adhere to the AMC. In the multivariate analysis, non-adherence was found to be significantly associated with traveling solo or with friends, traveling to southeast Asia and longer travel duration. The most common reason for non-adherence among travelers was the perception that the risk of contracting malaria is low (N = 251, 73.8%). Conclusion: In this study, 85% of the Israeli travelers did not adhere to the AMC, especially those traveling solo or with friends, visiting southeast Asia and for a long period. Counselors at the pre-travel clinics should stress the importance of AMC in highly endemic countries and consider alternative treatment strategies, especially in low risk areas or long duration travel, such as short-term schedule or reserve AMC for field trips.